Treatment of Acne with Herbal Remedie –Calendula officinalis: An Overview - Mishra, Priyanka (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAcne is a common problem that affects about 90% of teenagers. It occurs during a time of low self-esteem and high concern about appearance. There are many acne products on the market, and making an appropriate selection can be daunting. Common therapies that are used for the treatment of acne include topical, systemic, hormonal, herbal and combination therapy. Topically used agents are benzoyl peroxide, antibiotics and retinoid. Systemically used agents are antibiotics and isotretinoin. These drugs produce a number of potential side effects and development of resistance to frequently used antibiotics. This leads to treatment failure with previously used successful therapy. A variety of herbs, such as Tea tree, Aloe Vera, Neem, Tulsi, Marigold, Sea buck thorn, Turmeric etc. are used to treat acne. These are very safe and effective. This review focuses on the use of herb i.e. Calendula officinalis (Marigold) for the treatment of acne vulgaris that have been found to be very safe and effective.